Measurement of the B0 and B+ meson lifetimes with fully reconstructed hadronic final states - Aubert, B; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Palano, A; Chen, G; Chen, J; Qi, N; et al. (2001)
An overview is given on lifetime measurements based on a sample of approximately 23 million BB̄ pairs recorded near the Y(4S) resonance with the BABAR detector. The determined B0 and B+ meson lifetimes and their ratio are highlighted.